ANALISIS PERILAKU KONSUMEN DALAM BERBELANJA PADA PEDAGANG KELILING DAN PEDAGANG PASAR DI DESA KARANGREJO KEDIRI - Pebrianti, Wahyu; Seodjoko, Dodi Kusuma Hadi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
The study aims to analyze the factors affecting consumers in shopping for traveling traders and market traders in Karangrejo Village based on cultural, social, personal, and psychological factors.  This study is a descriptive qualitative study using a phenomenological approach. It uses qualitative research methods, by conducting observations, interviews, and documentation as data collection techniques. The informant selection uses 3R criteria: Relevance, Representation, Realignment. Triangulation used is source triangulation. The results of this study explain the behavior of consumers with 5 informants, from the research results with 5 informants, it is mostly due to time factors with time differences in shopping at traveling traders and market traders. This study recommendation is given to traveling traders and market traders, as well as for future researchers.